Optical Emission Spectroscopy of an Atmospheric Pressure Plasma Jet during Tooth Bleaching Gel Treatment. Issue 11 (November 2015) - Šantak, Vedran; Zaplotnik, Rok; Tarle, Zrinka; Milošević, Slobodan
Optical emission spectroscopy was performed during atmospheric pressure plasma needle helium jet treatment of various tooth-bleaching gels. When the gel sample was inserted under the plasma plume, the intensity of all the spectral features increased approximately two times near the plasma needle tip and up to two orders of magnitude near the sample surface. The color change of the hydroxylapatite pastille treated with bleaching gels in conjunction with the atmospheric pressure plasma jet was found to be in correlation with the intensity of OH emission band (309 nm). Using argon as an additive to helium flow (2 L/min), a linear increase (up to four times) of OH intensity and, consequently, whitening (up to 10%) of the pastilles was achieved. An atmospheric pressure plasma jet activates bleaching gel, accelerates OH production, and accelerates tooth bleaching (up to six times faster).